2-[(5-Methyl-1,3,4-thiadiazol-2-yl)sulfanyl]-N′-(4-nitrobenzylidene)acetohydrazide monohydrate - Murugan Nidhishree; Sundaramoorthy Gomathi; Jeyaraman Selvaraj Nirmalram; Logesh Mathivathanan (IUCrData)
In the title hydrate, C12H11N5O3S2·H2O, the dihedral angle between the aromatic rings is 9.6 (3)°. In the crystal, N—H...O and O—H...N hydrogen bonds link the components into (101) sheets.